General Education Teacher Educators and English Language Learner Teacher Preparation: Infusion as Curricular Change. Issue 4 (2nd October 2019) - de Jong, Ester; Naranjo, Cindy
ABSTRACT: To address the needs of English Language Leaners (ELLs) in grade-level content-area classrooms, teacher education programs are moving toward "infused" models of instruction where preservice general education courses include ELL-specific content. Little is known about how this curricular change is accomplished. To address this gap, this qualitative study examined how general teacher educators address ELL-specific content in their courses. Through the analysis of syllabi and semi-structured interviews with eleven instructors, our study identified curricular changes at the inclusive level, where ELL content is infused in general education courses. We argue for the need to transform the curriculum further to better acknowledge the diversity within ELLs and their specific linguistic and cultural strengths.